Observation of the increase in turn-on delay of quantum cascade lasers under pulsed electrical pumping with finite rise time. (December 2020) - Cherotchenko, E D; Dudelev, V V; Mikhailov, D A; Losev, S N; Babichev, A V; Gladyshev, A G; Novikov, I I; Lutetskiy, A V; Veselov, D A; Slipchenko, S O; Pikhtin, N A; Karachinsky, L Ya; et al.
Abstract: We demonstrate the experimental measurements of the turn-on delay in InAs-and InP-based quantum cascade lasers operating under pulsed electrical pumping with non-zero rise time. We report the unexpected delay time dependence on the pumping current density, that does not agree with available theoretical predictions. Performed numerical simulation of the model based on rate equations is only in qualitative, but not quantitative, agreement with our observations.